Removal of COD and Ammoniacal-Nitrogen from Industrial Wastewater using Adsorption with Plantain Husk Adsorbent - AKINYEMI Olusegun P.; NKEMDILIM Favour A. (International Journal of Engineering and Management Research, 2022)
The rate of depletion of ground/surface water has increased due to the weakness in the existing laws, contamination of the ground water and excess usage of water that produce increased quantity of wastewater. In this study, wastewater from Dangote Fertilizer Limited (DFL) was treated using adsorption method of treatment with consideration of the factors (pH, temperature and contact time) that impedes the efficiency of the method. Plantain husk, which is an agricultural waste, was used as adsorbent in the adsorption process. Response Surface Methodology (RSM) was used to determine the experimental number of runs after which it gives the optimum conditions of those parameters considered. The plantain husk was characterized using Gas chromatograph with Flame Ionization detector (GC-FID). The results obtained in the study revealed that utilization of the plantain husk as adsorbent in adsorption process for the removal of COD and Ammoniacal nitrogen from industrial wastewater will yield a high percentage removal (values). Ammoniacal nitrogen removal with plantain husk adsorbent was about 93% maximum and as pH increased to 7.5 (alkaline), a slight decrease in the Ammoniacal nitrogen removal percentage to about 92% could be attained. Furthermore, percentage removal of COD from the wastewater of about 83% maximum could be obtained. Effect of temperature on COD removal is a direct correlation as increase in temperature could lead to the decrease in COD removal. It can be concluded that the interaction between contact time and pH as compared to other interactions has an overall positive effect in the adsorption process of Ammoniacal nitrogen removal from wastewater. Being an agricultural waste and environmentally friendly materials, adsorbent from plantain husk should be considered for treatment of industrial waste water for removal of COD and ammoniacal nitrogen.